2013
DOI: 10.1186/1824-7288-39-46
|View full text |Cite
|
Sign up to set email alerts
|

BiliCheck vs JM-103 in identifying neonates not at risk of hyperbilirubinaemia

Abstract: BackgroundTranscutaneous bilirubinometry is widely used to predict hyperbilirubinemia by using several devices. The aim of this study was to compare the predictive ability of BiliCheck vs JM-103 in identifying neonates not at risk of significant hyperbilirubinemia, putting the data obtained with the two instruments on our transcutaneous bilirubin nomogram built with the BiliCheck.MethodsTranscutaneous bilirubin (TcB) measurement was performed when jaundice appeared in newborn babies and/or just before discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…According to the statistical significant difference (P = 0.074) in this study, it can be concluded that measuring the level of bilirubin depends on the age of the baby; so this finding was inconsistent with our results, considering the lack of a significant correlation between the two variables [16].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…According to the statistical significant difference (P = 0.074) in this study, it can be concluded that measuring the level of bilirubin depends on the age of the baby; so this finding was inconsistent with our results, considering the lack of a significant correlation between the two variables [16].…”
Section: Discussioncontrasting
confidence: 56%
“…Unfortunately this is an invasive and painful method which compared to portable bilirubinometer devices is associated with some delays in revealing data and requires serial blood sampling [8]. The first attempt to measure bilirubin through the skin was carried out in 1960 [9]. Early devices were not accurate enough to detect bilirubin level effectively, but they improved gradually and nowadays these machines are used as a noninvasive, safe, painless and simple way to estimate the bilirubin level through the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The high NPV for the 75 th and 95 th percentiles also suggest that our nomograms for the two instruments can reliably estimate infants who are unlikely to develop significant hyperbilirubinemia from 24 to 96 hours of age. Romagnoli and colleagues were perhaps the only researchers that have explored the predictive ability of nomograms derived from both JM-103 and Bilichek [ 29 ]. The measurements below 75 th percentiles from both instruments were found to be highly predictive of infants who were unlikely to develop significant hyperbilirubinemia between 24 and 96 hours of age (NPV: 98.4 to 100%).…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous bilirubin (TcB) can be used as first step in order to reduce the number of invasive and painful blood sampling. BiliCheck TM (Respironics, Marietta, GA – USA) and JM-103 (Drager Medical Inc, Telford, Pennsylvania) are the two most used bilirubinometers in the studies conducted in the Italian population and both had good correlation with TSB values [ 21 , 22 , 32 , 33 ]. TSB measurement is always necessary when the level of bilirubin is high and for therapeutic decisions (evidence level 1b).…”
Section: Introductionmentioning
confidence: 99%